Cross sectional study on the relationship of retinal vascular diameter with hypertension and albuminuria - DING Ning; HUANG Wen; WANG Ning-li (Linchuang shenzangbing zazhi)
Objective A cross-sectional study was carried out in this paper to test the hypothesis that retinal vessel diameter might be correlated with renal microvascular abnormalities. Methods A population-based cross-sectional study was conducted in this paper based on the data of Handan eye study( HES). 5 541 of the 7577 participants had complete information on retinal vessel diameter,albuminuria and blood pressure. Results It was found after adjusting age,gender and other confounders,the narrowest retinal arterial diameter was correlated with an increased risk of albuminuria( multivariable OR: 1. 24,95% CI: 1. 02 ～ 1. 51). Exposure to both hypertension and retinal arterial narrowing would obviously increase the risk of albuminuria( multivariable OR: 1. 69,95% CI: 1. 31 ～ 2. 19). Conclusions It is concluded in this research that retinal arterial diameter is independently associated with albuminuria. Individuals with both hypertension and retinal arterial narrowing are more likely to develop albuminuria.